Therapy of hereditary angioedema: is it time to focus on a different strategic approach? psychosocial issues and stress management - Rathinam, Jeyalalitha (International Journal of Basic & Clinical Pharmacology, 2017)
Hereditary angioedema is an autosomal dominant genetic disorder due to the deficiency of CI esterase inhibitor with elevated levels of bradykinin. The disorder was named hereditary angioneurotic edema because of the associated mental stress which exacerbated the condition. It manifests most often as edema of the skin and mucosal surfaces. Laryngeal edema can cause fatal obstruction. The various treatment modalities available for HAE includes plasma derived C1-INH concentrate, ecallantide, icatibant, attenuated androgens and fresh frozen plasma. The drugs for HAE are efficacious, but with side effects and are expensive. Patients with HAE exhibit anxiety and depression, and the stressful state by itself predisposes to further attacks which in the long run forms a vicious cycle one leading on to the other. Considering the fact that HAE is a chronic disorder needing meticulous attention, together with the task of home therapy, availability of medication, adverse effects of drugs, the economic burden and the undue compromise on quality of life, there definitely arises a need for focus on a different strategic approach towards treatment. Currently the focus is on various treatment modalities targeting the complement system and the acute symptomatology of the condition, rather than on the “neurotic component or the stress factor” which might prove to be one major area of therapeutic benefit. Management of stress related factors, overcoming anxiety and depression through psychosocial modalities and simple alternative therapies like yoga as a part of routine activity can greatly reduce the disease, as well as the economic burden and improve the quality of life.